Commentary: Blockholder Structures and Power Mechanisms in Family Firms. (March 2018) - Cacciotti, Gabriella; Ucbasaran, Deniz
We extend the work of Fattoum-Guedri, Guedri, and Delmar (2018) by suggesting that the number of family blockholders moderates the relationship between the distribution of voting power between family and nonfamily blockholders and firm performance. Building on power and negotiation theories, we argue that the participation of multiple generations of family members in the firm's ownership leads to greater diversity of perspectives that generates potential conflict over the distribution of resources. We highlight four power mechanisms—potential power, perceived power, power games, and realized power—to explain why family blockholders' conflicting and/or misaligned preferences, objectives, and visions for the family firm might influence the nature of the negotiation between the family and the nonfamily blockholder and impact family firm performance. We offer directions for future research.